TOF-SIMS study of red sealing-inks on paper and its forensic applications - Lee, Jihye; Lee, Chiwoo; Lee, Kangbong; Lee, Yeonhee (ELSEVIER, 2008)
Red sealing-ink samples are frequently submitted to forensic laboratories for identification and comparison in a wide variety of criminal and civil cases. The non-destructive identification of sealing-inks on paper is of important to preserve as large an amount of a fraudulent check, forged document, or other such evidence as possible for use in legal proceedings. Time-of-flight secondary ion mass spectrometry (TOF-SIMS) for the analysis of red sealing-inks on paper surfaces was investigated. TOF-SIMS spectra were employed to identify elements and organic compounds in red sealing-inks. An analysis was performed on five sealing-inks of red color manufactured in Korea, Japan, and China. Several fibers from specific sealing-ink sample on paper can be removed leaving little evidence of tampering and can be distinguished from other sealing-inks. Overlapped area of sealing-ink and ballpoint pen in the document was also investigated in order to identify the sequence of recording. Therefore, this study shows that TOF-SIMS is a useful technique for the non-destructive analysis of red sealing-inks on paper. (C) 2008 Elsevier B.V. All rights reserved.